Methacrylated gelatin and taro stem insoluble dietary fiber edible composite film and preparation method thereof
Patent Information
- Application Number
- CN202611314616.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-09
AI Technical Summary
[0026](1)本发明首次将甲基丙烯酰化明胶与芋头茎不溶性膳食纤维相结合制备可食性复合膜,通过甲基丙烯酰化改性显著提升了明胶基体的力学性能、热稳定性和疏水性,同时利用芋头茎膳食纤维作为绿色增强填料,实现了农业废弃物的高值化利用。
Smart Images

Figure CN122878635A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of membrane materials technology, and in particular to an edible composite membrane of methacrylamide gelatin-insoluble dietary fiber from taro stems and its preparation method. Background Technology
[0002] With increasing global environmental awareness and the deepening of plastic bans, developing biodegradable and environmentally friendly food packaging materials to replace traditional petroleum-based plastics has become a research hotspot and urgent need in the fields of food science and materials engineering. Among many bio-based materials, gelatin has been widely studied and applied in the preparation of edible films due to its wide availability, good biocompatibility, edibility, and excellent film-forming properties. However, pure gelatin films have inherent defects such as insufficient mechanical strength, poor water resistance, and easy moisture absorption, which seriously limit their practical application as packaging materials.
[0003] To overcome the aforementioned bottlenecks, the industry currently mainly optimizes gelatin through two technical routes: chemical modification and composite with reinforcing phases. For example, Li Chenhui et al. (Li Chenhui, Huang Li, Bai Shuyan, et al. Preparation of gelatin-polysaccharide composite membrane and its effect on lipid oxidation of refrigerated rainbow trout [J]. Food and Fermentation Industries, 2024, 50(19): 209-215.) combined chitosan, pectin and other polysaccharides with gelatin, and the prepared composite membrane had a better preservation effect on rainbow trout; this method improved the water vapor permeability and light transmittance of the gelatin membrane, but it had defects such as insufficient mechanical strength and moisture barrier properties. For example, the study by Pan, Ling; Li, Peng; Tao, Yubo. (2020). Preparation and Properties of Microcrystalline Cellulose / Fish Gelatin Composite Film. Materials, 13(19), 4370–. doi:10.3390 / ma13194370 showed that the addition of microcrystalline cellulose can significantly improve the tensile strength and modulus of fish bladder gelatin composite film, but the thermal stability and elongation at break are significantly reduced.
[0004] It is evident that in existing technologies, due to differences in film-forming components and membrane processing techniques, the structure and properties of membranes vary significantly. The overall performance of these membranes is relatively weak, with only one property being superior. For example, some membranes may have high mechanical strength, but other properties such as thermal stability and elongation at break are relatively weak, often failing to meet practical requirements. Therefore, it is essential to design an edible membrane with high overall performance and practical value.
[0005] By combining methacrylamide gelatin with insoluble dietary fiber from taro stems, and through systematic extraction, modification, and compounding, it is hoped that the structural stability of the methacrylamide gelatin crosslinking network and the reinforcing and barrier effects of dietary fiber can be synergistically utilized to prepare high-performance edible composite films. However, there is currently no technical route for combining methacrylamide gelatin with insoluble dietary fiber from taro stems, and there are no reports on its use in preparing edible composite films. Summary of the Invention
[0006] The purpose of this invention is to address the aforementioned problems by providing an edible composite film of taro stem insoluble dietary fiber and methacrylamide gelatin, along with its preparation method. This invention improves the performance of the gelatin matrix through methacrylic anhydride modification and utilizes insoluble dietary fiber extracted from taro stems as a green reinforcing filler. The composite film is prepared through a casting process, resulting in an edible composite film with excellent comprehensive performance. This not only provides a new approach for the resource utilization of taro stem waste but also offers a new solution for developing high-performance, fully bio-based edible packaging materials, aligning with the sustainable development strategy.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] An edible composite film of taro stem insoluble dietary fiber and methacrylamide gelatin, characterized in that it comprises the following components by weight: 0.5-3 parts methacrylamide gelatin, 0.1-0.6 parts insoluble dietary fiber, 1.5-9 parts glycerin, 2-12 parts starch, and the balance being water;
[0009] The insoluble dietary fiber is prepared by the following method: taro stem powder is defatted, and then subjected to a first bleaching treatment, an alkali treatment, a second bleaching treatment, an acid hydrolysis treatment, a dialysis treatment, and a freeze-drying treatment to obtain the insoluble dietary fiber.
[0010] Preferably, the defatting treatment is performed as follows: taro stem powder is ultrasonically treated in ethyl acetate to obtain defatted taro stem powder; the primary bleaching treatment is performed as follows: defatted taro stem powder is mixed with sodium hypochlorite solution, the pH is adjusted to acidic, and bleached in a heated water bath; after bleaching, it is filtered and washed until neutral to obtain the primary bleached product, named cellulose C1; the alkali treatment is performed as follows: cellulose C1 is placed in sodium hydroxide solution, soaked under heating conditions, then stirred, filtered, and washed until neutral to obtain the alkali-treated product, named cellulose C2; the secondary bleaching treatment is performed as follows: cellulose C2 is bleached again using the primary bleaching treatment method, and the product obtained from the secondary bleaching treatment is named cellulose C3; the acid hydrolysis is performed as follows: sulfuric acid is added to cellulose C3, and ultrasonic hydrolysis is performed under heating conditions; after hydrolysis, the sulfuric acid solution is removed by centrifugation.
[0011] Preferably, during defatting treatment, the solid-liquid ratio of taro stem powder to ethyl acetate is 1:5 g / ml; during the first bleaching treatment, the solid-liquid ratio of defatted taro stem powder to sodium hypochlorite solution is 1:120 g / ml; during alkali treatment, the solid-liquid ratio of cellulose C1 to sodium hydroxide solution is 1:200 g / ml; during the second bleaching treatment, the solid-liquid ratio of cellulose C2 to sodium hypochlorite solution is 1:120 g / ml; and during acid hydrolysis, the solid-liquid ratio of cellulose C3 to sulfuric acid is 4:20~24 g / ml.
[0012] Preferably, the concentration of the sodium hypochlorite solution is 8–12% w / v, the pH of the bleaching treatment is 4, the temperature is 65–85℃, and the time is 1–3 h; the concentration of the sodium hydroxide solution is 0.5–1 mol / L, the temperature of the alkali treatment is 50–70℃, and the time is 2–4 h; the concentration of the sulfuric acid used for acid hydrolysis is 45–50% w / v, the temperature of the ultrasonic hydrolysis is 50–70℃, and the time is 0.5–2 h; the dialysis treatment method is to put the precipitate obtained by acid hydrolysis centrifugation into a dialysis bag and dialyze until neutral. The specifications of the dialysis bag can be selected according to the actual situation, as long as the nanocellulose is retained and the acid and small molecule byproducts are filtered out. A 3500 Da dialysis bag is preferred.
[0013] The starch is preferably water chestnut starch.
[0014] In addition, this application also provides a method for preparing the edible composite film, comprising the following steps:
[0015] (1) Preparation of insoluble dietary fiber: Taro stem powder is defatted, and then subjected to bleaching, alkali treatment, bleaching, acid hydrolysis, dialysis and freeze drying in sequence to obtain the insoluble dietary fiber.
[0016] (2) Preparation of methacrylamide gelatin: Add gelatin to pure water and heat and stir until completely dissolved; add sodium carbonate and sodium bicarbonate and continue stirring until completely dissolved; add methacrylic anhydride and stir under heating conditions; after the reaction is completed, dialyze to neutral and freeze dry to obtain the methacrylamide gelatin.
[0017] (3) Preparation of composite film: According to the weight ratio, the methacrylated gelatin, taro stem insoluble dietary fiber and glycerin are added to water, mixed evenly and homogenized to obtain methacrylated gelatin-dietary fiber mixture; starch is added to water to obtain starch solution, shaken and heated to gelatinize to obtain starch gelatinized liquid; the methacrylated gelatin-dietary fiber mixture and the starch gelatinized liquid are mixed evenly and homogenized, allowed to stand to eliminate bubbles, poured into a mold and dried to obtain the edible composite film.
[0018] Preferably, in step (2) of the above preparation method, the mass ratio of gelatin to water is 1:7.5; the mass ratio of gelatin to sodium carbonate and sodium bicarbonate is 1:0.2:0.16; and the solid-liquid ratio of gelatin to methacrylic anhydride is 10:1 g / ml.
[0019] Preferably, in the above preparation method, in step (2), the temperature for stirring and dissolving gelatin, sodium carbonate and sodium bicarbonate is 40-60 °C; the temperature for heating and stirring after adding methacrylic anhydride is 50-70 °C, and the time is 3-5 h.
[0020] Preferably, in step (3) of the above preparation method, when preparing the methacrylated gelatin-dietary fiber mixture, the solid-liquid ratio of the methacrylated gelatin to water is 5:100 g / ml.
[0021] Preferably, in step (3) of the above preparation method, when preparing the starch gelatinized liquid, the solid-liquid ratio of starch to water is 1:20 g / ml; the specific steps of starch heating and gelatinization are as follows: the starch solution after shaking for 8 to 10 minutes is placed in a water bath at 90 to 100°C and heated for 15 to 25 minutes; during heating, it is taken out and shaken every 5 minutes.
[0022] Preferably, in step (3) of the above preparation method, the homogenization time after mixing the methacrylated gelatin-dietary fiber mixture with the starch gelatinized liquid is 2-5 min; the time for standing to eliminate bubbles is 1-3 h; and the drying temperature is 50-70 ℃ and the time is 5-10 h.
[0023] Methacrylamide gelatin is a photocrosslinking material obtained by modifying gelatin with methacrylic anhydride. The double bonds introduced on its molecular chain can form a covalent crosslinking network under ultraviolet light initiation, thereby significantly improving the mechanical strength, stability and hydrophobicity of the material.
[0024] Taro stems, a major byproduct of taro production, are rich in cellulose and are an ideal raw material for extracting high-quality insoluble dietary fiber. Taro stem dietary fiber has good water retention and adsorption properties. Introducing it as a reinforcing phase into a biopolymer matrix can fill, strengthen, and improve the network structure. Therefore, extracting dietary fiber from agricultural waste as a reinforcing phase for gelatin membranes can not only achieve high-value utilization of resources but also improve the mechanical and barrier properties of composite membranes.
[0025] In summary, due to the adoption of the above technical solution, the present invention has the following beneficial effects:
[0026] (1) This invention is the first to combine methacrylated gelatin with insoluble dietary fiber from taro stems to prepare an edible composite film. The mechanical properties, thermal stability and hydrophobicity of the gelatin matrix are significantly improved by methacrylation modification. At the same time, the dietary fiber from taro stems is used as a green reinforcing filler, realizing the high-value utilization of agricultural waste.
[0027] (2) This invention addresses the problems of strong hydrophilicity and structural instability of gelatin by modifying it with methacrylamide, introducing hydrophobic groups and covalent cross-linking networks. The prepared insoluble dietary fiber has a large specific surface area, high reactivity, and rigid particle reinforcement due to the nano-size effect. It has high crystallinity and can form a dense hydrogen bond network with the gelatin matrix through physical filling and hydrogen bond cross-linking, constructing a dense physical barrier. This physical barrier can also combine with the chemical cross-linking network formed by methacrylamide modification to form a more stable and dense double network structure, reducing interface defects and free volume. Only a small amount of insoluble dietary fiber is needed to significantly improve the tensile strength, thermal stability, and moisture barrier properties of the composite membrane, while maintaining good transparency, thus significantly improving the overall performance of the composite membrane. It is evident that there is a significant synergistic effect between methacrylamide modification and the prepared insoluble dietary fiber in this invention. Furthermore, the insoluble dietary fiber prepared in this invention belongs to nanocellulose crystals. Experimental data show that the composite membrane prepared by this invention has a tensile strength of 0.542 MPa, a significantly reduced water vapor permeability coefficient, a water solubility reduced to 23.79%, and a swelling rate reduced to 87.29%.
[0028] (3) The preparation method of the present invention is simple and controllable, suitable for industrial production. The composite film obtained has good mechanical properties, barrier properties and water resistance, and can be used as a packaging material for edible food. Attached Figure Description
[0029] Figure 1 This is a comparison chart of the tensile strength of various composite films.
[0030] Figure 2 This is a comparison chart of the elongation at break of various composite membranes.
[0031] Figure 3 This is a comparison chart of the transmittance of various composite films.
[0032] Figure 4 A color comparison chart of various cellulose molecules and composite membranes.
[0033] Figure 5 This is a comparison chart of the moisture content of various composite membranes.
[0034] Figure 6 A comparison chart of the water vapor permeation coefficients of various composite membranes.
[0035] Figure 7 This is a comparison chart of the water solubility of various composite membranes.
[0036] Figure 8 This is a comparison chart of the swelling rates of various composite films.
[0037] Figure 9 This is the FT-IR spectrum of the composite membrane. Detailed Implementation
[0038] This application provides an edible composite film of taro stem insoluble dietary fiber and methacrylamide gelatin. The composite film is composed of the following parts by weight: 0.5-3 parts methacrylamide gelatin, 0.1-0.6 parts insoluble dietary fiber, 1.5-9 parts glycerol, 2-12 parts starch, and the balance being water.
[0039] The insoluble dietary fiber is prepared by the following method:
[0040] Taro stem powder was placed in ethyl acetate at a solid-liquid ratio of 1:5 g / ml and subjected to ultrasonic degreasing treatment.
[0041] Then, defatted taro stem powder was mixed with sodium hypochlorite solution with a concentration of 8-12% w / v at a solid-liquid ratio of 1:120 g / ml. The pH was adjusted to acidic, preferably pH 4. The mixture was then subjected to a first bleaching treatment in a water bath heated to 65-85℃ for 1-3 hours. After bleaching, the mixture was filtered and washed until neutral to obtain the first bleached product, which was named cellulose C1.
[0042] Next, cellulose C1 was placed in a sodium hydroxide solution with a concentration of 0.5-1 mol / L at a solid-liquid ratio of 1:200 g / ml and soaked at 50-70 °C for 2-4 hours. Then, the solution was stirred, filtered, and washed until neutral to obtain the alkali-treated product, which was named cellulose C2.
[0043] Then, following the method of the first bleaching treatment, cellulose C2 was mixed with sodium hypochlorite solution with a concentration of 8-12% w / v at a solid-liquid ratio of 1:120 g / ml for a second bleaching treatment. The product obtained from the second bleaching treatment was named cellulose C3.
[0044] Finally, sulfuric acid with a concentration of 45-50% w / v was added to cellulose C3 at a solid-liquid ratio of 4:20~24 g / ml, and ultrasonic hydrolysis was carried out at 50-70 ℃ for 0.5-2 h. After hydrolysis, the sulfuric acid solution was removed by centrifugation.
[0045] The precipitate obtained by acid hydrolysis and centrifugation is placed in a dialysis bag and dialyzed until neutral. The size of the dialysis bag can be selected according to the actual situation, as long as the nanocellulose is retained and the acid and small molecule byproducts are filtered out. A 3500 Da dialysis bag is preferred. Then, the insoluble dietary fiber is obtained by freeze drying.
[0046] In addition, this application also provides a method for preparing the composite membrane, comprising the following steps:
[0047] (1) Following the above steps, the taro stem powder was defatted, and then successively subjected to bleaching, alkali treatment, secondary bleaching, acid hydrolysis, dialysis and freeze drying to prepare insoluble dietary fiber.
[0048] (2) Preparation of methacrylamide gelatin: Add gelatin to pure water, heat to 40-60 °C and stir until completely dissolved; add sodium carbonate and sodium bicarbonate, and continue stirring at 40-60 °C until completely dissolved; add methacrylic anhydride and stir to react at 50-70 °C; after the reaction is complete, dialyze to neutral, freeze dry to obtain the methacrylamide gelatin; wherein, the mass ratio of gelatin to water is 1:7.5, the mass ratio of gelatin to sodium carbonate and sodium bicarbonate is 1:0.2:0.16; the solid-liquid ratio of gelatin to methacrylic anhydride is 10:1 g / ml;
[0049] (3) Preparation of composite membrane:
[0050] According to the weight ratio, the methacrylamide gelatin, taro stem insoluble dietary fiber and glycerin were added to water together, wherein the solid-liquid ratio of methacrylamide gelatin to water was 5:100 g / ml. After the above raw materials were mixed evenly, they were homogenized to obtain a methacrylamide gelatin-dietary fiber mixture.
[0051] Add starch to water, preferably water chestnut starch, with a solid-liquid ratio of starch to water of 1:20 g / ml. After mixing, a starch solution is obtained. The starch solution, after shaking for 8-10 minutes, is placed in a water bath at 90-100℃ and heated for 15-25 minutes. During heating, it is taken out and shaken every 5 minutes to obtain a starch gelatinized liquid.
[0052] After the methacrylated gelatin-dietary fiber mixture is mixed evenly with the starch gelatinized liquid, it is homogenized for 2-5 minutes, allowed to stand to eliminate air bubbles for 1-3 hours, poured into a mold, and dried at 50-70 ℃ for 5-10 hours to obtain the edible composite film.
[0053] To more clearly illustrate the present invention, the following specific embodiments will be used to further explain the invention.
[0054] Example 1: This example describes the preparation of an edible composite film of methacrylamide gelatin and taro stem insoluble dietary fiber. The specific preparation method includes the following steps:
[0055] (1) Preparation of insoluble dietary fiber:
[0056] ① Defatting treatment: Crush taro stems into taro stem powder, pass through a 60-mesh sieve, then place 20g of taro stem powder in 100mL of ethyl acetate and sonicate for 2 hours. After filtration, defatted taro stem powder is obtained.
[0057] ② First bleaching treatment: Mix 1g of defatted taro stem powder with 120ml of 10% (w / v) sodium hypochlorite, adjust the pH of the solution to 4 with acetic acid (1 mol / L), then bleach in a 75℃ water bath for 2 hours, then filter and wash until neutral to obtain the first bleaching product, named cellulose C1.
[0058] ③Alkali treatment: Place 1g of cellulose C1 in 200ml of 0.5 mol / L NaOH and soak at 60 ℃ for 3 hours. Then stir, filter and wash until neutral to obtain the alkali-treated product, named cellulose C2.
[0059] ④ Secondary bleaching treatment: 1g of cellulose C2 was mixed with 120ml of 10% (w / v) sodium hypochlorite and bleached again using the same method as the first bleaching treatment. The product obtained from the secondary bleaching treatment was named cellulose C3.
[0060] ⑤ Acid hydrolysis: Add 2.4 ml of 48% (w / v) sulfuric acid to 0.4 C3 of cellulose and sonicate at 60 °C for 1 hour, stirring once every 30 minutes during the heating process; remove the residual sulfuric acid solution by centrifugation at 4000 r / min for 20 minutes;
[0061] ⑥ Dialysis treatment: Place the precipitate into a 3500 Da dialysis bag and dialyze until neutral.
[0062] ⑦ The insoluble dietary fiber was obtained by freeze-drying and named cellulose C4;
[0063] (2) Preparation of methacrylamide gelatin: 20 g of gelatin was added to 150 g of pure water and heated to 50 °C and stirred until completely dissolved; 4 g of sodium carbonate and 3.2 g of sodium bicarbonate were added and stirred at 50 °C until completely dissolved; 2 mL of methacrylic anhydride was added and stirred at 60 °C for 4 h; after the reaction was completed, the mixture was dialyzed to neutral and freeze-dried to obtain the methacrylamide gelatin.
[0064] (3) Preparation of composite film: 0.5 g of methacrylamide gelatin, 0.1 g of taro stem insoluble dietary fiber (i.e., cellulose C4) and 1.5 g of glycerol were added to 10 ml of water, shaken for 30 min to mix evenly, and then homogenized for 2 min to obtain methacrylamide gelatin-dietary fiber mixture; 2 g of water chestnut starch was added to 40 ml of water to obtain starch solution, shaken for 10 min and then heated in a water bath at 100℃ for 20 min to gelatinize, taking it out and shaking it every 5 min to ensure complete starch gelatinization, and obtaining starch gelatinized liquid; the methacrylamide gelatin-dietary fiber mixture and the starch gelatinized liquid were mixed evenly and homogenized for 3 min, and then allowed to stand for 2 h to eliminate air bubbles, poured into a mold and allowed to stand for 15 min, and then placed in an oven and baked at 60 ℃ for 7 h to obtain the edible composite film.
[0065] Comparative Example 1
[0066] Compared with Example 1, the difference in this comparative example is that steps (1) and (2) are omitted, and a gelatin film without methacrylamide modification and without cellulose is prepared. The specific preparation method is as follows:
[0067] Add 0.5g of gelatin and 1.5g of glycerin to 10ml of water, shake for 30min to mix evenly, and then homogenize for 2min to obtain a gelatin solution; add 2g of water chestnut starch to 40ml of water to obtain a starch solution, shake for 10min, and then heat in a 100℃ water bath for 20min to gelatinize, shaking every 5min to ensure complete starch gelatinization, to obtain a starch gelatinized solution; mix the gelatin solution and the starch gelatinized solution evenly, homogenize for 3min, let stand for 2h to eliminate air bubbles, pour into a mold and let stand for 15min, then bake in an oven at 60℃ for 7h to obtain the gelatin film.
[0068] Comparative Example 2
[0069] Compared with Example 1, the difference in this comparative example is that steps ③④⑤⑥⑦ after “② first bleaching treatment” in step (1) are omitted, step (2) is omitted, the gelatin used in step (3) is gelatin that has not been modified by methacrylamide, and the cellulose used is cellulose C1.
[0070] Comparative Example 3
[0071] Compared with Example 1, the difference of this comparative example is that steps ④⑤⑥⑦ after “③ alkali treatment” in step (1) are omitted, step (2) is omitted, the gelatin used in step (3) is gelatin that has not been modified by methacrylamide, and the cellulose used is cellulose C2.
[0072] Comparative Example 4
[0073] Compared with Example 1, the difference of this comparative example is that steps ⑤⑥⑦ after “④ secondary bleaching treatment” in step (1) are omitted, step (2) is omitted, the gelatin used in step (3) is gelatin that has not been modified by methacrylamide, and the cellulose used is cellulose C3.
[0074] Comparative Example 5
[0075] Compared with Example 1, the difference in this comparative example is that step (2) is omitted, and the gelatin used in step (3) is gelatin that has not been modified by methacrylamide.
[0076] Comparative Example 6
[0077] Compared with Example 1, the difference in this comparative example is that step (1) is omitted, and a cellulose-free methacrylamide gelatin film is prepared. The specific preparation method is as follows:
[0078] 0.5 g of methacrylamide gelatin film and 1.5 g of glycerol were added to 10 ml of water, shaken for 30 min to mix evenly, and then homogenized for 2 min to obtain methacrylamide gelatin solution. 2 g of water chestnut starch was added to 40 ml of water to obtain starch solution, shaken for 10 min, and then heated in a water bath at 100 ℃ for 20 min to gelatinize. During the process, the solution was taken out and shaken every 5 min to ensure complete starch gelatinization, resulting in starch gelatinized solution. The methacrylamide gelatin solution and the starch gelatinized solution were mixed evenly and homogenized for 3 min. The mixture was allowed to stand for 2 h to eliminate air bubbles, poured into a mold and allowed to stand for 15 min. The mixture was then placed in an oven and baked at 60 ℃ for 7 h to obtain the methacrylamide gelatin film.
[0079] Comparative Example 7
[0080] Compared with Example 1, the difference in this comparative example is that steps ③④⑤⑥⑦ after “② first bleaching treatment” in step (1) are omitted, and the cellulose used in step (3) is cellulose C1.
[0081] Comparative Example 8
[0082] Compared with Example 1, the difference in this comparative example is that steps ④⑤⑥⑦ after “③ alkali treatment” in step (1) are omitted, and the cellulose used in step (3) is cellulose C2.
[0083] Comparative Example 9
[0084] Compared with Example 1, the difference in this comparative example is that steps ⑤⑥⑦ after “④ secondary bleaching treatment” in step (1) are omitted, and the cellulose used in step (3) is cellulose C3.
[0085] Comparative Example 10
[0086] Compared with Example 1, the difference in this comparative example is that after obtaining cellulose C3 in step (1) "④ Secondary bleaching treatment", acid hydrolysis, dialysis treatment and freeze drying are not performed. Instead, cellulose C5 is bleached three times according to the secondary bleaching treatment method. The cellulose used in step (3) is cellulose C5.
[0087] Comparative Example 11
[0088] Compared with Example 1, the difference in this comparative example is that after obtaining cellulose C1 in step (1) "② First bleaching treatment", no alkali treatment or second bleaching treatment is performed. Instead, C1 is directly subjected to acid hydrolysis, dialysis treatment and freeze drying in the manner of Example 1 to obtain cellulose C6; the cellulose used in step (3) is cellulose C6.
[0089] Comparative Example 12
[0090] Compared with Example 1, the difference in this comparative example is that after obtaining cellulose C2 by "③ alkali treatment" in step (1), a secondary bleaching treatment is not performed. Instead, C2 is directly subjected to acid hydrolysis, dialysis treatment and freeze drying in the manner of Example 1 to obtain cellulose C7. The cellulose used in step (3) is cellulose C7.
[0091] The formulations of the composite membranes prepared in each embodiment and comparative example are shown in Table 1 below:
[0092]
[0093] Performance testing
[0094] The composite films prepared in each embodiment and comparative example were tested for properties such as thickness, color difference, mechanical properties, light transmittance, moisture content, water vapor transmission coefficient, water solubility, and swelling rate. The results are as follows.
[0095] 1. Thickness test
[0096] The thicknesses of the composite films showed no significant differences, ranging from 0.0944 to 0.1211 mm, indicating that the film formation process was relatively stable and the system composition did not have a significant impact on the film thickness.
[0097] 2. Color difference test
[0098] The color difference parameters of the film sample were measured using a colorimeter, including the brightness value (ΔL*), red-green difference (Δa*), and yellow-blue difference (Δb*), and the total color difference value (ΔE) was calculated. The results are shown in Table 2.
[0099]
[0100] The results showed that in both ordinary gelatin and methacrylamide gelatin systems, the color of the composite membranes exhibited a clear and regular change after the addition of taro stem dietary fiber of different purification levels. The C1 fiber obtained from the first purification contained more residual natural pigments, causing the Δb value of the methylgelatin composite membrane to increase from 8.75 to 16.41, resulting in a significantly higher Δb value and a deeper yellow hue. After multiple bleaching treatments, the pigments in cellulose C2 and cellulose C3 were continuously removed, and the Δb values decreased to 11.91 and 11.42, respectively, with the yellow hue of the composite membrane gradually decreasing. The composite membrane prepared from cellulose C4, obtained through further acid hydrolysis and ultrasonic treatment, had a Δb value of 10.97, had the least impact on the overall color of the composite membrane, and exhibited the best color.
[0101] In addition, cellulose C5 undergoes a third bleaching process compared to cellulose C3, resulting in more thorough pigment removal. Therefore, the Δb value of the composite membrane prepared in Comparative Example 10 is lower than that in Comparative Example 9. However, due to the lack of acid hydrolysis, it cannot achieve the same effect as cellulose C4 in removing colored small molecule impurities, thus its Δb value is higher than that in Example 1. Cellulose C6 does not undergo alkali treatment or secondary bleaching. Even after acid hydrolysis, pigment molecules remain firmly bound to the fiber surface and cannot be removed. Therefore, the Δb value of the composite membrane prepared in Comparative Example 11 is similar to that in Comparative Example 7. Cellulose C6 undergoes direct acid hydrolysis after alkali treatment. Due to the lack of a second bleaching process to remove colored impurities and residual lignin, the Δb value of the composite membrane prepared in Example 12 is higher than that in Example 1.
[0102] Therefore, the degree and method of purification of taro stem dietary fiber are important factors in controlling the color of composite membranes. The cellulose C4 obtained by the purification method of this application (first bleaching → alkali treatment → second bleaching → sulfuric acid hydrolysis and dialysis) can minimize the impact on the appearance and color of the membrane.
[0103] 3. Mechanical performance testing
[0104] (1) Tensile strength analysis
[0105] Depend on Figure 1It can be seen that the tensile strength of the blank gelatin membrane without cellulose addition is basically close to that of the methacrylamide gelatin membrane. Furthermore, with the increase of cellulose purity, internal impurities are continuously removed, and the regularity and rigidity of the molecular structure are significantly improved, forming a stable reinforcing system in the gelatin and methacrylamide gelatin matrices, thus increasing the tensile strength of the composite membrane. Among them, highly purified cellulose C4 exhibits the best mechanical reinforcing effect: when the added cellulose is cellulose C4, the tensile strength of the C4-gelatin membrane reaches 0.452 MPa, which is the maximum tensile strength value of the gelatin-based composite membrane in this experiment; the tensile strength of the C4-methacrylamide gelatin composite membrane shows a more significant improvement, reaching 0.542 MPa, which is the maximum tensile strength value of all composite membranes in this experiment.
[0106] This is mainly because the surface of cellulose C4 has abundant hydroxyl groups, which can form hydrogen bonds with amino and carboxyl groups on gelatin molecules, playing a role in building a skeleton and giving the membrane a dense network structure. This dense hydrogen bond network forms a dense physical barrier, thereby improving tensile strength and breaking strength. Furthermore, the number of hydrophilic groups in the methacrylated gelatin obtained through methacrylation modification is reduced, resulting in lower hydrophilicity and significantly enhanced water resistance. It also forms a stable network with a more stable structure, enhancing the biocompatibility between methacrylated gelatin and fiber. The physical barrier constructed by insoluble dietary fiber and gelatin can also combine with the chemical cross-linking network formed by methacrylation modification to form a more stable and dense double network structure. Therefore, through the synergistic effect between methacrylation modification and the prepared insoluble dietary fiber, the composite membrane prepared from methacrylated gelatin and cellulose C4 has superior mechanical properties.
[0107] While cellulose C5 also has high purity, it lacks acid hydrolysis, is not nano-sized, has a small specific surface area, and has far fewer hydrogen bonding sites with methacrylamide gelatin than cellulose C4. Furthermore, the amorphous regions are not removed, resulting in weaker fiber rigidity and lower tensile strength compared to cellulose C4. Although cellulose C6 underwent acid hydrolysis to improve its crystallinity, the lack of alkali treatment and a second bleaching process resulted in a large number of impurities. These impurities disrupt the integrity of the methacrylamide gelatin crosslinking network, interfering with matrix continuity and severely reducing tensile strength. Cellulose C7, through alkali treatment to remove some impurities and acid hydrolysis to increase crystallinity and rigidity, exhibits better tensile strength than the composite film of Comparative Example 12 compared to Comparative Example 8. However, due to the lack of a second bleaching process, residual impurities still hinder some hydrogen bond formation, resulting in lower tensile strength than Comparative Example 9 and Example 1.
[0108] (2) Elongation at break analysis
[0109] from Figure 2It can be seen that, for both gelatin-based and methacrylated gelatin-based composite films, the elongation at break first increases and then decreases with increasing cellulose purity. This is mainly because, from cellulose C1 to cellulose C3, as the degree of purification increases, cellulose impurities decrease, and the hydrogen bonding with gelatin is enhanced, thus improving toughness and elongation at break. Cellulose C4, prepared through acid hydrolysis and dialysis, removes the amorphous aggregates, resulting in high crystallinity and enhanced molecular modulus. Due to the hydrogen bonding between the nanocellulose nanoparticles, a three-dimensional rigid network structure is formed in the matrix, leading to a slight decrease in elongation at break. However, the overall good deformation adaptability is still maintained, and the slight sacrifice in flexibility does not affect the actual performance of the film, achieving a balance between high strength and usable toughness.
[0110] In addition, the abundance of hydrophilic groups such as hydroxyl, carboxyl, and amino groups on gelatin molecules gives it strong hydrophilicity, making it prone to strong swelling and even dissolution, resulting in poor toughness. On the other hand, methacrylated gelatin has reduced hydrophilicity, increased molecular chain flexibility, and lower C1 purity, which has a weaker restrictive effect on molecular chain movement and cannot form a rigid network in the methacrylated gelatin matrix. Therefore, composite films with methacrylated gelatin bases have higher elongation at break than composite films with gelatin bases, whether without cellulose or with added cellulose C1.
[0111] However, when higher purity cellulose C2-C7 is added, the elongation at break of the ordinary gelatin system surpasses that of the methacrylamide system. This is because as the purity and crystallinity of cellulose increase, the fiber rigidity strengthens and forms a rigid network in the matrix, restricting molecular chain movement. Methacrylamide gelatin itself has high structural stability and its molecular chain movement is more restricted, resulting in a more significant decrease in toughness after the increase in rigidity. Ordinary gelatin, however, is physically cross-linked, with higher molecular chain flexibility, and can still undergo significant deformation, thus resulting in a higher elongation at break.
[0112] 4. Transparency Test
[0113] from Figure 3As can be seen, methacrylylation modification reduced the transmittance of the gelatin film from 31.9% to 25.2%, mainly because the modification disrupted the original hydrogen bond network of gelatin, increasing light scattering centers and thus reducing transmittance. Adding cellulose C1-C4 further reduced the transmittance of the composite film, and the transmittance gradually decreased with increasing fiber purification. This is primarily because cellulose and gelatin form a relatively dense network structure, leading to a decrease in transmittance. The synergistic effect between methacrylylation modification and cellulose C4 was most significant; therefore, the C4-methacrylylated gelatin film prepared in Example 1 showed the greatest decrease in transmittance, dropping to 17.6%. Cellulose C5 was only bleached multiple times without acid hydrolysis or nano-sizing, resulting in a larger fiber size than cellulose C4 and a stronger light scattering effect. Therefore, the composite membrane of Example 10 has a higher transmittance than that of Example 1. Cellulose C6 was not purified multiple times and has extremely poor compatibility with gelatin, resulting in a membrane with many defects and an artificially high transparency due to increased interfacial porosity. Cellulose C7 was nano-sized by acid hydrolysis and removed some impurities by alkali treatment. Therefore, the composite membrane of Comparative Example 12 forms a denser network than Comparative Examples 8 and 9, and its transmittance is lower than that of Comparative Examples 8 and 9. However, due to residual impurities, its density is still not as good as that of Example 1, so its transmittance is slightly higher than that of Example 1.
[0114] It should be noted that: (1) the transmittance of gelatin film and methacrylamide-modified gelatin film is different because methacrylamide gelatin is colored, and the quality of the film should be considered from the properties of gelatin film and methacrylamide gelatin; (2) as can be seen from the experiments mentioned above, different colors of film are obtained by doping different types of cellulose, such as Figure 4 As shown, Figure 4 Using red paper as a reference, the membrane was placed at the bottom of the red paper. After comprehensive comparison, it was found that cellulose C2 was whiter than cellulose C2 membrane that had undergone secondary bleaching, and the color of C2-methacrylamide gelatin was also whiter than that of C3-methacrylamide gelatin membrane. It can also be clearly seen that the color of C4-methacrylamide gelatin with added cellulose C4 in this application is the whitest. (3) Under the same thickness and water content conditions, the transmittance of pure gelatin membrane and methacrylamide modified gelatin membrane in the visible light region (500–800 nm) is very high. However, the advantage of methacrylamide modified gelatin membrane is not that it has "higher absolute transmittance", but that the cross-linked network is stable, the refractive index is well matched, and the optical performance does not degrade during long-term use. Although pure gelatin membrane has good intrinsic transmittance, its structure is easily changed under physiological conditions, and its actual transmittance performance may be unstable.
[0115] Analysis shows that although the transmittance of the C4-methacrylamide gelatin film prepared in Example 1 was the lowest among all groups, the transmittance of 17.6% does not affect the actual use of the film. Moreover, compared with the significant improvement in core properties such as mechanical properties and water resistance, the slight decrease in the transmittance of the composite film is within an acceptable range.
[0116] 5. Moisture content test
[0117] The moisture content of gelatin film reflects its equilibrium water absorption capacity under ambient humidity conditions. This indicator is closely related to the hydrophilicity / hydrophobicity and the density of the film's structure.
[0118] Test results are as follows Figure 5 As shown, methylation modification can effectively reduce the moisture content of gelatin membranes. By introducing hydrophobic methacrylyl groups into the gelatin molecular chain, hydrophilicity is reduced, and the moisture content decreases from 46.49% to 44.92%. The moisture content of the composite membrane further decreases with the degree of cellulose purification after adding cellulose C1-C4. The core mechanism is that cellulose and gelatin form hydrogen bonds, increasing membrane density and hindering the permeation and adsorption of water molecules. Among them, the C4-methacrylated gelatin membrane prepared in Example 1 has the lowest moisture content, only 36.73%, which is about 8.2% lower than the pure methacrylated gelatin membrane and about 9.8% lower than the ordinary gelatin membrane. This also reflects the synergistic effect between methacrylation modification and cellulose C4. This synergistic effect is that the hydrophobicity brought by methacrylated gelatin and the membrane density of cellulose C4 jointly construct a denser network structure.
[0119] However, the purification method also affects the water content of the membrane. Although cellulose C5 has high purity and reduces hydrophilic impurities, the micron-sized cellulose C5 cannot build a dense physical barrier like the nano-sized cellulose C4. The water molecule diffusion path is shorter, and the barrier performance is only slightly improved, which is significantly weaker than the dual-network synergistic effect of Example 1. Cellulose C6 contains a large amount of unremoved hydrophilic hemicellulose and impurities. These impurities have a strong water absorption and swelling capacity and severely damage the cross-linking network of methacrylamide gelatin, resulting in a loose membrane structure, easy water penetration, and extremely poor water resistance. Its performance is close to that of a blank methacrylamide gelatin membrane without added cellulose. Although cellulose C7 has enhanced local crystallinity through acid hydrolysis, residual impurities still provide water adsorption sites and destroy the complete hydrogen bond network, resulting in weak water resistance.
[0120] 6. Barrier performance test
[0121] (1) Water vapor transmission coefficient
[0122] Depend on Figure 6It can be seen that the changes in the water vapor permeation coefficient of each composite membrane are mainly affected by the combined effects of methacrylylation modification, the addition of cellulose, and the nano-sizing of cellulose.
[0123] After methacrylization modification, gelatin molecules can form a more stable chemical cross-linking structure, making the membrane denser. Simultaneously, the number of hydrophilic groups is reduced, lowering the adsorption capacity for water molecules. Therefore, the water vapor permeability coefficient of pure methacrylized gelatin membranes is lower than that of ordinary gelatin membranes. Adding taro stem dietary fiber further enhances the membrane's moisture-blocking performance. The nano-treated cellulose C4 shows the most significant effect, primarily because compared to cellulose C1, C2, and C3, cellulose C4 undergoes deep purification and nano-processing, resulting in smaller particle size, more uniform dispersion, and a larger specific surface area. Nanofibers can form a physical barrier within the membrane and form numerous hydrogen bonds with gelatin molecules, increasing the system's density and extending the water vapor diffusion path, thus providing a stronger boost to moisture-blocking performance. Furthermore, there is a significant synergistic effect between methacrylized modified gelatin and nano-cellulose C4: the chemical cross-linking network formed by methacrylization combines with the physical barrier formed by cellulose C4 to form a more stable and dense dual-network structure, reducing interfacial defects and free volume, making it even more difficult for water vapor to permeate.
[0124] Although cellulose C6 and cellulose C7 were also nano-sized by acid hydrolysis, the purification methods of cellulose C6 and cellulose C7 differed from those in Example 1, and impurities were not completely removed. After film formation, the impurities damaged the cross-linking structure, resulting in weak barrier ability and a high water vapor permeability coefficient.
[0125] In summary, methacrylylation modification can improve the barrier properties of the membrane through cross-linking structure, while dietary fiber, especially nanocellulose, can further reduce the water vapor permeability coefficient through physical barriers and hydrogen bonding. The synergistic effect of these two factors enables the C4-methacrylylated gelatin composite membrane prepared in Example 1 to exhibit optimal moisture barrier performance, showing promising application prospects as an edible packaging material.
[0126] (2) Water solubility
[0127] from Figure 7 It can be concluded that the water solubility of the composite membrane with methacrylamide gelatin matrix is significantly lower than that of the membrane with unmodified gelatin matrix under the same dietary fiber conditions. The water solubility of the methacrylamide gelatin membrane is 8.32% lower than that of the gelatin membrane. This is because the methacrylamide group is a hydrophobic group. After the gelatin is modified by methacrylamide, a hydrophobic group is introduced, which reduces the affinity of gelatin molecules for water molecules, thereby reducing the water solubility of the membrane material and effectively solving the problem that natural gelatin membranes are easily soluble in water.
[0128] Both gelatin-based membranes and methacrylamide-based membranes showed reduced water solubility after the introduction of dietary fiber compared to the control group without added dietary fiber. This is because cellulose contains a large number of hydroxyl groups on its surface, which can form numerous hydrogen bonds with the polar groups on the gelatin molecular chains, enhancing the interfacial interaction between the two phases. This interaction improves the structural stability of the composite membrane, significantly improving its water resistance and effectively inhibiting its dissolution by aqueous solutions, thus reducing water solubility. membrane Water solubility of materials
[0129] Furthermore, as the purification level of cellulose increases, the reduction in water solubility is generally greater. Specifically, the water solubility of C4-ordinary gelatin membranes decreased to 25.54%; the water solubility of C4-methacrylamide gelatin composite membranes decreased to 23.79% due to the interaction between methacrylamide-modified gelatin and nanocellulose C4. Methacrylamide modification reduces the mobility of water molecules, while nanocellulose C4 increases the resistance to membrane dissolution. However, there are exceptions. For example, although cellulose C5 in Comparative Example 10 has high purity, it cannot construct a dense physical barrier like cellulose C4, resulting in limited improvement in barrier properties and inability to effectively inhibit the dissolution of the composite membrane.
[0130] The above results demonstrate that methacrylization modification can effectively reduce the water solubility of gelatin films. Adding dietary fiber on this basis can further reduce the water solubility of the films. The method of combining methacrylized modified gelatin and dietary fiber can effectively improve the water resistance of gelatin films, indicating that there is a synergistic reinforcing effect between methacrylized modified gelatin and nanocellulose C4.
[0131] (3) Swelling rate
[0132] Swelling rate is an important indicator for evaluating the water resistance of gelatin films.
[0133] like Figure 8 As shown, the swelling rate of the gelatin film was 180.71%, while that of the methacrylamide gelatin film was 173.04%. This indicates that methacrylamide modification can effectively reduce the swelling rate, mainly because methacrylamide modification introduces hydrophobic groups, which reduces the affinity of gelatin for water molecules and enables the construction of a stable network.
[0134] After adding dietary fiber C1-C4, the swelling rates of both gelatin-based membranes and methacryloylated gelatin-based membranes showed a decreasing trend: Experimental data showed that in the gelatin-based membrane system, the swelling rate of C4-gelatin membrane decreased to 125.80%; in the methacryloylated gelatin-based system, the swelling rate of C4-methacryloylated gelatin membrane decreased to 87.29%. This is because the strong hydrogen bonding between cellulose and gelatin effectively improves the water resistance of gelatin. Among all samples, the C4-methacryloylated gelatin membrane had the lowest swelling rate, which is attributed to the interaction between methacrylation modification and nanocellulose C4. Specifically, the methacryloyl group is a hydrophobic group, and nanocellulose C4 and methacryloylated gelatin can form a dense hydrogen bond network, constructing a stable structure and maximally suppressing membrane swelling.
[0135] In the comparative examples with added cellulose C5-C7, cellulose C5 undergoes a third bleaching process to further remove impurities, resulting in higher membrane density than cellulose C3. The swelling rate of the composite membrane in Comparative Example 10 is lower than that in Comparative Example 9. However, due to the lack of acid hydrolysis, a large-area nanofiber physical barrier cannot be constructed, and the swelling rate is significantly higher than that in Example 1. Cellulose C6 and cellulose C7 omit the bleaching and / or alkali treatment processes, resulting in high impurity content. Consequently, the composite membranes prepared have numerous internal interface defects and poor hydrogen bond network continuity, leading to a swelling rate far higher than that in Example 1.
[0136] It is evident that, in the barrier performance test, the C4-methacrylamide gelatin film prepared in Example 1 exhibits strong advantages in terms of water vapor barrier, water solubility, and swelling rate.
[0137] 7. Fourier Transform Infrared Spectroscopy (FTIR) Analysis
[0138] like Figure 9 As shown, all samples exhibited characteristic absorptions at 3290 cm⁻¹ (N–H / O–H stretching vibration), 2935 cm⁻¹, and 2885 cm⁻¹ (C–H stretching vibration); lignin characteristic peaks (~1500 cm⁻¹) were also observed. -1 The disappearance of amide peaks and the enhancement of cellulose characteristic peaks were observed. After methacrylation modification, the characteristic peaks of amide I and II bands shifted significantly, confirming that the methacryloyl group underwent an acylation reaction with the gelatin amino group. The C=C double bond absorption peak overlapped with the amide I band and was difficult to distinguish. The shift of the absorption peaks in the fingerprint region at 1150 cm⁻¹, 1023~1026 cm⁻¹, and 844~925 cm⁻¹ further indicates that cellulose C3 and C4 can form hydrogen bonds and covalent interactions with gelatin with the methacryloyl group. All samples retained complete amide characteristic peaks, indicating that the modification did not destroy the gelatin polypeptide backbone.
[0139] Based on the above performance tests, it can be seen that methacrylation modification can significantly improve the mechanical strength and water barrier properties of gelatin films. Dietary fiber, as a rigid filler, can further enhance the film, reduce swelling, and improve moisture barrier properties. Dietary fiber C4, which has been purified to a certain degree through a specific purification method, can maximize the mechanical strength and water resistance of the composite film and has good barrier properties. It can effectively solve the technical defects of traditional gelatin films, such as low strength, easy swelling, and poor barrier properties, by sacrificing only some light transmittance and flexibility.
[0140] The above description is a detailed description of the preferred embodiments of the present invention. However, the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modifications made under the technical spirit of the present invention should fall within the patent scope covered by the present invention.
Claims
1. A methacrylamide gelatin-based edible composite film containing insoluble dietary fiber from taro stems, characterized in that, The product comprises the following components by weight: 0.5–3 parts methacrylamide gelatin, 0.1–0.6 parts insoluble dietary fiber, 1.5–9 parts glycerin, 2–12 parts starch, and the remainder being water. The insoluble dietary fiber is prepared by the following method: taro stem powder is defatted, and then subjected to a first bleaching treatment, an alkali treatment, a second bleaching treatment, an acid hydrolysis treatment, a dialysis treatment, and a freeze-drying treatment to obtain the insoluble dietary fiber.
2. The edible composite film according to claim 1, characterized in that, The defatting process is as follows: Taro stem powder is placed in ethyl acetate and ultrasonically treated to obtain defatted taro stem powder. The operation method of the first bleaching process is as follows: defatted taro stem powder is mixed with sodium hypochlorite solution, the pH is adjusted to acidic, and bleached in a heated water bath; after bleaching, the mixture is filtered and washed until neutral to obtain the first bleached product, named cellulose C1. The alkaline treatment method is as follows: cellulose C1 is placed in a sodium hydroxide solution and soaked under heating conditions. Then, it is stirred, filtered, and washed until neutral to obtain the alkaline-treated product, which is named cellulose C2. The operation method of the secondary bleaching treatment is as follows: Cellulose C2 is bleached again using the same method as the primary bleaching treatment, and the product obtained from the secondary bleaching treatment is named cellulose C3. The acid hydrolysis operation method is as follows: sulfuric acid is added to cellulose C3, and ultrasonic hydrolysis is carried out under heating conditions. After hydrolysis is completed, the sulfuric acid solution is removed by centrifugation.
3. The edible composite film according to claim 2, characterized in that, During defatting, the solid-liquid ratio of taro stem powder to ethyl acetate was 1:5 g / ml; during the first bleaching treatment, the solid-liquid ratio of defatted taro stem powder to sodium hypochlorite solution was 1:120 g / ml; during alkali treatment, the solid-liquid ratio of cellulose C1 to sodium hydroxide solution was 1:200 g / ml; during the second bleaching treatment, the solid-liquid ratio of cellulose C2 to sodium hypochlorite solution was 1:120 g / ml; and during acid hydrolysis, the solid-liquid ratio of cellulose C3 to sulfuric acid was 4:20~24 g / ml.
4. The edible composite film according to claim 2, characterized in that, The concentration of the sodium hypochlorite solution is 8–12% w / v, the pH of the bleaching treatment is 4, the temperature is 65–85℃, and the time is 1–3 h; the concentration of the sodium hydroxide solution is 0.5–1 mol / L, the temperature of the alkali treatment is 50–70℃, and the time is 2–4 h; the concentration of the sulfuric acid used for acid hydrolysis is 45–50% w / v, the temperature of the ultrasonic hydrolysis is 50–70℃, and the time is 0.5–2 h; the dialysis treatment is performed by placing the precipitate obtained from the acid hydrolysis centrifugation into a dialysis bag and dialyzing until neutral.
5. A method for preparing an edible composite film according to any one of claims 1-4, characterized in that, Includes the following steps: (1) Preparation of insoluble dietary fiber: Taro stem powder is defatted, and then subjected to bleaching, alkali treatment, bleaching, acid hydrolysis, dialysis and freeze drying in sequence to obtain the insoluble dietary fiber. (2) Preparation of methacrylamide gelatin: Add gelatin to pure water and heat and stir until completely dissolved; add sodium carbonate and sodium bicarbonate and continue stirring until completely dissolved; add methacrylic anhydride and stir under heating conditions; after the reaction is completed, dialyze to neutral and freeze dry to obtain the methacrylamide gelatin. (3) Preparation of composite film: According to the weight ratio, the methacrylated gelatin, taro stem insoluble dietary fiber and glycerin are added to water, mixed evenly and homogenized to obtain methacrylated gelatin-dietary fiber mixture; starch is added to water to obtain starch solution, shaken and heated to gelatinize to obtain starch gelatinized liquid; the methacrylated gelatin-dietary fiber mixture and the starch gelatinized liquid are mixed evenly and homogenized, allowed to stand to eliminate bubbles, poured into a mold and dried to obtain the edible composite film.
6. The edible composite film according to claim 5, characterized in that, In step (2), the mass ratio of gelatin to water is 1:7.5; the mass ratio of gelatin to sodium carbonate and sodium bicarbonate is 1:0.2:0.16; and the solid-liquid ratio of gelatin to methacrylic anhydride is 10:1 g / ml.
7. The edible composite film according to claim 5, characterized in that, In step (2), the temperature for stirring and dissolving gelatin, sodium carbonate and sodium bicarbonate is 40-60 °C; after adding methacrylic anhydride, the temperature for heating and stirring is 50-70 °C, and the time is 3-5 h.
8. The edible composite film according to claim 5, characterized in that, In step (3), when preparing the methacrylated gelatin-dietary fiber mixture, the solid-liquid ratio of the methacrylated gelatin to water is 5:100 g / ml.
9. The edible composite film according to claim 5, characterized in that, In step (3), when preparing the starch gelatinized solution, the solid-liquid ratio of starch to water is 1:20 g / ml; the specific steps for heating and gelatinizing starch are as follows: the starch solution after shaking for 8 to 10 minutes is placed in a water bath at 90 to 100°C and heated for 15 to 25 minutes; during heating, it is taken out and shaken every 5 minutes.
10. The edible composite film according to claim 5, characterized in that, In step (3), the homogenization time after mixing the methacrylated gelatin-dietary fiber mixture with the starch gelatinized liquid is 2-5 min; the time for standing to eliminate bubbles is 1-3 h; and the drying temperature is 50-70 ℃ and the time is 5-10 h.